2006
DOI: 10.1086/504836
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Evolution of the Ionizing Background and the Epoch of Reionization withz ~ 6 Quasars. II. A Sample of 19 Quasars

Abstract: We study the evolution of the ionization state of the intergalactic medium (IGM) at the end of the reionization epoch using moderate resolution spectra of a sample of nineteen quasars at 5.74 < z em < 6.42 discovered in the Sloan Digital Sky Survey. Three methods are used to trace IGM properties: (a) the evolution of the Gunn-Peterson (GP) optical depth in the Lyα, β, and γ transitions; (b) the distribution of lengths of dark absorption gaps, and (c) the size of HII regions around luminous quasars. Using this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

97
1,341
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,340 publications
(1,456 citation statements)
references
References 108 publications
97
1,341
7
Order By: Relevance
“…First, the dot-hatched region in Fig. 9 shows models where reionization completes 5.8 zion 6.6, as inferred from the spectra of high-redshift QSOs (Fan et al 2006;Bolton et al 2011;McGreer et al 2015); these are also shown by the solid diamonds and open squares in Fig. 10.…”
Section: Other Reionization Constraintsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, the dot-hatched region in Fig. 9 shows models where reionization completes 5.8 zion 6.6, as inferred from the spectra of high-redshift QSOs (Fan et al 2006;Bolton et al 2011;McGreer et al 2015); these are also shown by the solid diamonds and open squares in Fig. 10.…”
Section: Other Reionization Constraintsmentioning
confidence: 92%
“…Attempts have also been made to measure the ionization state of the IGM directly. Reionization is relatively wellconstrained to be completed at z 6 by analysis of the Gunn-Peterson effect (Gunn & Peterson 1965) in the spectra of high-redshift QSOs (e.g., Fan et al 2006;Willott et al 2007;Bolton et al 2011;McGreer et al 2015) and gammaray bursts (GRBs, e.g., Chornock et al 2013). Preliminary measurements of the IGM neutral fraction at z ∼ 7-8 have been made using the Lyα emission fraction of star-forming galaxies (e.g., Stark et al 2010;Treu et al 2013;Pentericci et al 2014;Tilvi et al 2014;Faisst et al 2014;Schenker et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As of today, the main observational constraints on reionization come from the CMB polarization data (e.g., those from the WMAP and Planck experiments, Planck Collaboration et al 2013a) and the quasar absorption spectra at z 5.5 (Fan et al 2006). Detailed models which are able to match these and a variety of other observations predict the reionization to be process extended over 6 z 15.…”
Section: Introductionmentioning
confidence: 99%
“…The fainter magnitude limit, corresponding to atomic cooling halos of mass M h ∼ 10 9 M , is fully consistent with the Planck results, considering the uncertainty in the reionization model parameters. This calculation shows that ultrafaint galaxies can in principle provide enough photons to fully reionize the universe by z ∼ 6 to match observations of the Lyα forest (Fan et al 2006). Both magnitude limits are broadly consistent with a range of constraints from observations, within the reionization model uncertainty: UV luminosity densities (Finkelstein et al 2012) for observable galaxies; quasar near zones (Venemans et al 2015); quasar spectra damping wings (Schroeder et al 2013); GRB spectra damping wings (McQuinn et al 2008); transmission (Fan et al 2006) and dark gaps (McGreer et al 2015) in the Lyα forest; and the clustering of Lyα emitting galaxies (Ouchi et al 2010).…”
Section: Q(z)mentioning
confidence: 62%
“…We plot our results from integrating the model UV LFs to two magnitude limits of Mab = −17 (green) and Mab = −12 (purple), with 1σ confidence regions as shaded regions. We also plot constraints derived from observations of: Lyα emission from galaxies (open circles, Ouchi et al 2010;Pentericci et al 2014;Tilvi et al 2014;Faisst et al 2014;Schenker et al 2014); the Lyα forest (filled circles, Fan et al 2006); the clustering of Lyα emitting galaxies (square, Ouchi et al 2010); GRB spectra damping wings (diamond, McQuinn et al 2008); dark gaps in the Lyα forest (upper triangles, McGreer et al 2015); quasar near zones (star, Venemans et al 2015); and quasar spectra damping wings (lower triangle, Schroeder et al 2013). We also plot the Planck Collaboration et al (2015) redshift of instantaneous reionization.…”
Section: Q(z)mentioning
confidence: 99%